The European development fund education - training 1958 - 1980 - Directorate General - Information (Luxemburg Office for Official Publications of the European Communities, 1983)
This report reviews the activities of the European community in the area of Education and Training in the overseas countries and territories (OCT) and developing nations of Africa, the Caribbean and the Pacific (ACP). This study covers the aid provided through the European Development Fund (EDF) from 1958 to 1980
Includes bibliographical references
osc 04/03/2019
Loans
Keywords: Education